2015
DOI: 10.4238/2015.january.30.9
|View full text |Cite
|
Sign up to set email alerts
|

Association of the ApoE gene polymorphism and dietary factors with cerebral infarction and circulating lipid concentrations

Abstract: ABSTRACT. The aim of this study was to explore the relationship between the ApoE gene polymorphism and dietary factors with stroke and circulating lipid levels in the Chinese population. We selected 580 patients with stroke and 580 age-and gender-matched healthy controls, and examined their ApoE polymorphism genotype using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. We also analyzed the relationship between the ApoE gene polymorphism and dietary factors as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Serum lipid levels are closely correlated with dietary habits, [ 12 ] which in Shandong are quite different from other areas of China. Shandong cuisine is famous for its high salt and soy sauce content, and sodium intakes were high among residents of Shandong province.…”
Section: Introductionmentioning
confidence: 99%
“…Serum lipid levels are closely correlated with dietary habits, [ 12 ] which in Shandong are quite different from other areas of China. Shandong cuisine is famous for its high salt and soy sauce content, and sodium intakes were high among residents of Shandong province.…”
Section: Introductionmentioning
confidence: 99%
“…In a statistical analysis of anthropometric and clinical characteristics between APOE ε4 carriers and non-carriers, only heart rate was significantly higher in APOE ε4 carriers than in non-carriers in both Lao Loum and minorities. Several reports demonstrated that APOE ε4 is associated with AD[ 40 ], cognitive decline[ 21 ], depressive symptoms[ 22 ], stroke[ 23 , 24 ], hypertension[ 25 , 26 ], coronary heart disease[ 24 , 26 ], cardiovascular[ 27 , 28 ], and diabetes[ 29 , 30 ]. Very few studies have addressed the relationship between APOE ε4 and heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the incidence of AD may be attributable to lifestyle and nutrition [ 4 , 6 , 16 20 ]. On the other hand, APOE ε4 is associated not only with AD but also with cognitive decline[ 21 ], depressive symptoms[ 22 ], stroke[ 23 , 24 ], hypertension[ 25 , 26 ], coronary heart disease[ 24 , 26 ], cardiovascular disease[ 27 , 28 ], and diabetes[ 29 , 30 ]. In combination with environmental factors, APOE ε4 may influence the risk of non-communicable diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors and poor habits are two main causes of cerebral infarction (26). According to an epidemiological study, hyperlipidemia and hypertension are two important factors that greatly increase the risk of cerebral infarction (2).…”
Section: Original Investigationmentioning
confidence: 99%